2009
DOI: 10.1186/1743-7075-6-20
|View full text |Cite
|
Sign up to set email alerts
|

White Tea extract induces lipolytic activity and inhibits adipogenesis in human subcutaneous (pre)-adipocytes

Abstract: Background: The dramatic increase in obesity-related diseases emphasizes the need to elucidate the cellular and molecular mechanisms underlying fat metabolism. To investigate how natural substances influence lipolysis and adipogenesis, we determined the effects of White Tea extract on cultured human subcutaneous preadipocytes and adipocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 25 publications
4
50
0
1
Order By: Relevance
“…As other researches have shown the green tea extract is an effective adjunct to reduce LDL andit is well tolerated [16], the results of the current study demonstrated highly significant (p<0.01) hypolypidemic effect in treated groups compared to the control group, while its level was significantly improved in GT+ rifampin treated rats compared to the rifampin group. Our results showed that the effect of WT on blood lipid profile was more efficient than green tea in dose dependent manner.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…As other researches have shown the green tea extract is an effective adjunct to reduce LDL andit is well tolerated [16], the results of the current study demonstrated highly significant (p<0.01) hypolypidemic effect in treated groups compared to the control group, while its level was significantly improved in GT+ rifampin treated rats compared to the rifampin group. Our results showed that the effect of WT on blood lipid profile was more efficient than green tea in dose dependent manner.…”
Section: Discussionsupporting
confidence: 57%
“…The Toxic effects of rifampicin on animals and plants are well documented [1]. Based on these data, green and white tea extracts were tested in this study for their effects on rifampin induced hepatic injuries in male rats through assessment of lipid profile, liver enzyme and antioxidant capacity [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These recent studies have also indicated that EGCG improves cholesterol metabolism through the upregulation of LDL receptor and also reduces extracellular apoB levels (38). In addition, sterol regulatory element-binding proteins-1c (SREBP-1c), C/EBP-β, and peroxisome proliferator-activated receptor-γ (PPAR-γ), also are involved in the cholesterol-lowering effect of EGCG (39,40). However, effects of EGCG on ABCA1, which plays a key role in the process of RCT, have rarely been described until now.…”
Section: Discussionmentioning
confidence: 98%
“…15 White tea leaves extract was reported to inhibit adipogenesis and stimulate lipolytic activity. 16 Another study also reported that white tea leaves ethanolic extract has an antidiabetic activity as inhibitor α-glucosidase, α-amylase, and dipeptidyl peptidase IV.…”
Section: Discussionmentioning
confidence: 97%